Dietary Supplementation of Baicalein Affects Gene Expression in Broiler Adipose Tissue During the First Week Post-hatch - Xiao, Yang; Halter, Bailey; Boyer, Casey; Cline, Mark A.; Liu, Dongmin; Gilbert, Elizabeth R. (Frontiers in Physiology, 2021)
Dietary supplementation of baicalein, a flavonoid, has anti-obesity effects in mammals and broiler chickens. The aim of this study was to determine the effect of dietary baicalein supplementation on broiler growth and adipose tissue and breast muscle deposition. Fifty Hubbard × Cobb-500 day-of-hatch broiler chicks were assigned to a control starter diet or control diet supplemented with 125, 250, or 500 mg/kg baicalein and diets were fed for the first 6 days post-hatch. Body weight, average daily body weight gain, and average daily food intake were all reduced by 500 mg/kg baicalein. Breast muscle and subcutaneous and abdominal fat weights were also reduced in chicks that consumed the baicalein-supplemented diets. mRNAs for genes encoding factors involved in adipogenesis and fat storage, 1-acylglycerol-3-phosphate-O-acyltransferase 2, CCAAT/enhancer-binding protein β, perilipin-1, and sterol regulatory element-binding transcription factor 1, were more highly expressed in the adipose tissue of broilers supplemented with baicalein than the controls, independent of depot. Diacylglycerol acyltransferase and peroxisome proliferator-activated receptor gamma mRNAs, involved in triacylglycerol synthesis and adipogenesis, respectively, were greater in subcutaneous than abdominal fat, which may contribute to differences in expansion rates of these depots. Results demonstrate effects of dietary supplementation of baicalein on growth performance in broilers during the early post-hatch stage and molecular effects in major adipose tissue depots. The mild reduction in food intake coupled to slowed rate of breast muscle and adipose tissue accumulation may serve as a strategy to modulate broiler growth and body composition to prevent metabolic and skeletal disorders later in life.